Improving the learning curve in monoportal endoscopic lumbar surgery: Development and validation of a porcine training model - Laura Olías-Ortiz; Rafael Llombart-Blanco; Gloria Abizanda-Sarasa; Isabel Lacave-Mas; Carmen Valverde-Gestoso; Matías Alfonso-Olmos (PLoS ONE, 2026)
Study design Experimental animal study. Purpose Endoscopic spine surgery (ESS) has gained substantial traction globally. Proficiency in ESS demands a steep learning curve and rigorous technical training. This study aims to develop and validate a porcine model as a high-fidelity, reproducible platform for hands-on training in lumbar endoscopic procedures. Methods Thirteen skeletally mature hybrid pigs (Landrace x Large White) underwent lumbar endoscopic decompression via a transforaminal approach at L4-L5 and an interlaminar approach at L5-L6. Specific procedural modifications were introduced to optimize anatomical correlation and surgical ergonomics. Following a seven-day postoperative period, necropsies were performed to evaluate procedural outcomes and adverse events. Operative times, intraoperative events, and postoperative outcomes were systematically recorded. Results Endoscopic decompression was successfully completed in all specimens. Mean operative time was 134.7 ± 32.3 minutes. Intraoperative complications occurred in 4 animals (30.8%): uncontrollable epidural bleeding (case 1), dural tear (case 7), technically difficult transforaminal access in a low-weight pig (33.8 kg, case 8), and a complex interlaminar approach leading to spinal cord injury (case 13). One additional animal (case 4) developed paraplegia without structural findings at necropsy, attributed to intraoperative positioning. Necropsy revealed asymptomatic epidural hematomas in three cases (9, 11, 12). Three animals (23.1%) required early euthanasia based on humane criteria. A significant learning curve effect was demonstrated, with operative time decreasing over the series (ρ = –0.73, p = 0.004). Conclusions The porcine lumbar spine provides a reliable and anatomically valid model for ESS training. Awareness of species-specific anatomy, specimen size, and positioning is essential to maximize reproducibility and safety.